Law Enforcement, Public Opinion, the Media, and its Effects - Borcyk, Aaron (2020)
The United States Bureau of Labor Statistics estimates that, in 2018, law enforcement workers made up about .8% of the country’s workforce. Given that they make up such a large percentage of the workforce plus the extreme public visibility of the profession by nature, law enforcement is a highly discussed topic. After the controversial officer-involved shootings of Michael Brown, Walter Scott, and Freddie Gray between 2014 and 2016 the credibility and integrity of law enforcement came into question. Law enforcement is depicted on many media platforms in many different ways; The current research leverages qualitative data obtained from in-depth oral interviews with 25 law enforcement officers (LEOs) from three Midwest agencies to provide insight into the perspectives of LEOs and how they feel the public and the media view and cover them and their work. Results suggested that participants believed no form of media or media outlet portrays law enforcement accurately and many participants opined that the law enforcement is, more often than not, portrayed in a negative light by national media. Approximately half of all participants stated that public perception of law enforcement was at least somewhat positive at the beginning of their career and over 90% of participants who responded to the question stated that that public perception of law enforcement has gotten worse since their careers began